The use of epigenetic phenomena for the improvement of sheep and cattle - Goddard, Michael E.; Whitelaw, Emma (Frontiers in Genetics, 2014)
This review considers the evidence for inheritance across generations of epigenetic marks and how this phenomenon could be exploited in the cattle and sheep industries. Epigenetic marks are chemical changes in the chromosomes that affect the expression of genes and hence the phenotype of the cell and are passed on during mitosis so that the daughter cells have the same chemical changes or epigenetic marks as the parent cell. Although most epigenetic marks are wiped clean in the process of forming a new zygote, some epigenetic marks (epimutations) may be passed on from parent to offspring. The inheritance of epigenetic marks across generations is difficult to prove as there are usually alternative explanations possible. There are few well documented cases, mainly using inbred strains of mice. The epimutations are unstable and revert to wild type after a few generations. Although, there are no known cases in sheep or cattle, it is likely that inherited epimutations occur in these species but it is unlikely that they explain a large part of the inherited or genetic variation. There is limited evidence in mice and rats that an environmental treatment can cause a change in the epigenetic marks of an animal and that this change can be passed on the next generation. If inherited epimutations occur in sheep and cattle, they will already be utilised to some extent by existing genetic improvement programs. It would be possible to modify the statistical models used in the calculation of EBVs to better recognise the variance controlled by epimutations, but it would probably have, at best, a small effect on the rate on genetic (inherited) gain achieved. The inheritance of epigenetic marks caused by the environment experienced by the sire offers a new opportunity in sheep and cattle breeding. However, at present we do not know if this occurs or, if it does, what environmental treatment might have a beneficial effect.